Acute Respiratory Distress Syndrome as a Precursor to Post–Intensive Care Syndrome. Issue 1 (January 2019) - McPeake, Joanne; Veith, Joshua; Maley, Jason; Mikkelsen, Mark E.
Abstract : More than 6 million patients are cared for in an intensive care unit annually in the United States, and millions more internationally. Acute respiratory failure (ARF) is a common indication for intensive care unit admission, one that afflicts more than half of critically ill patients. Acute respiratory distress syndrome (ARDS) is a severe, life-threatening form of ARF. With advances in care over the last 50 years, the majority of ARF and ARDS patients survive. The survivorship literature is largely one that describes functional impairments and reduced quality of life after critical illness. In this review article, we put forth the concept that ARDS is a precursor to post–intensive care syndrome, defined as new or worsening impairments in cognition, mental health, and/or physical health after critical illness. This "precursor" paradigm is suggested as a means to a better end for patients with ARDS, by detailing care provisions and strategies to optimize short-term and long-term outcomes.